Classification and microstructural stability of high generation single crystal Nickel-based superalloys - Roman Sowa; Sebastian Arabasz; Wojtan Magdalena Parlinska (Zaštita Materijala)
This paper presents a brief review on various types of single crystal Ni-based superalloys designed over the recent years. The design principles to achieve required mechanical properties and microstructural stability over the long time exposure to high temperatures are emphasized. The main attention is given to alloys with a high content of refractory elements. In particular the formation of brittle phases, like topologically close packed (TCP) phases, degrading mechanical properties of the Ni-based superalloys is emphasized.